PERANAN SEKOLAH DI MASA PANDEMI COVID-19 DALAM PERSPEKTIF SOSIOLOGI - Hikmat (GoAcademica Research dan Publishing, 2020)
The spread of Covid-19 has led to the closure of all schools in various countries around the world. This is a tragedy that happened for the first time in the world of education. Then this also raises a question, whether the community still needs schools as a social institution that can fulfill its functions during this pandemic. The purpose of this study is to see how schools play a role in carrying out their functions during the Covid-19 pandemic. This study found that schools could not fully carry out their two main functions, namely socialization and selection, during a pandemic because they needed to carry out school from home (SFH) activities. Then the implementation of the lockdown on schools also made it difficult to provide education for all students in schools.